Changes in contractile properties of wrestlers skeletal muscles during maximal intermittent isometric contractions - Skurvydas A.; Maciukas A.; Baceviciene R.; Liaugminas, A. (Education. Physical training. Sport, 1999)
The expression of contractile characteristics during physical work of maximal intensity depends on the influence of activating and suppressing mechanisms. Some of contractile characteristics may be more sensitive for the influence of activating mechanisms, muscle wisdom and other for the influence of suppressing ones. So the changing of contractile characteristics may be different. The aim of our research is to test the changing of efficiency of contraction and relaxation of quadriceps femoris m. at 6 times in 10 seconds of maximal efforts. Methods: 8 wrestlers at the age of 20±2 years participated in the experiment. Methods of electrostimulation and dynamometry were used to evaluate contractile properties of quadriceps femoris muscle. One pulse (Pt) and duplete stimuli (with interstimuli interval 10 ms) (Pd) were delivered transcutaneously (pulse duration 1ms). We stimulated and evaluated contraction characteristics of quadriceps femoris muscle at 8 Hz (P8) and 20 Hz (P20) frequencies. Experimental protocol: athletes performed 6 time (10 seconds duration) maximal voluntary knee extensions with 5 seconds recovery time between every session. Before the experiment and after each extension the following characteristics were measured: peak tension, contraction time and half relaxation time of evoked contraction, and MVC (maximal voluntary contraction). Results: The results show that the muscle force increases at first sessions of 10 seconds (10-30 s) maximal contraction due to muscle activation (posttetanic potentiation), then (30-40 s) muscle wisdom compensates the suppressing influence of metabolic fatigue and finally when muscle compensating mechanisms exhaust (50-60 s) the muscle force decreases due to prevalent metabolic fatigue factor.